Hubungan Antara Kecerdasan Emosional dengan Komunikasi Interpersonal dan Kinerja Karyawan di Perusahaan Makanan Tangerang Banten - Imam Muhammad Rizal; Masduki Asbari; Ahmad Nafis; Aulia Rizka; Nofiyanti Nofi (Yayasan Aya Sophia Indonesia, 2026)
This study aims to determine the relationship between emotional intelligence and interpersonal communication. Interpersonal communication in employees is an inseparable part of social relations in the company, this is because of the need for employees to be accepted in the company environment. Emotionally intelligent employees can understand and manage feelings well, and are able to understand and overcome the feelings of others. The population in this study were employees of PT. Gandummas Kencana consisting of 700 employees with a research sample of 50 employees. The sampling technique used the cluster random sampling technique. The measuring instruments used were the emotional intelligence scale (32 aitems, α = 0.876) and the interpersonal communication scale (35 aitems, α = 0.902). The results of this study indicate that there is a positive relationship between emotional intelligence and interpersonal communication of ???????????? = 0.678. Emotional intelligence provides an effective contribution of 46% to interpersonal communication